Low levels of Methyl-CpG binding protein 2 are accompanied by an increased vulnerability to the negative outcomes of stress exposure during childhood in healthy women - Cosentino, Livia; Zidda, Francesca; Dukal, Helene; Witt, Stephanie; De Filippis, Bianca; Flor, Herta (Translational Psychiatry, 2022)
Numerous mental illnesses arise following stressful events in vulnerable individuals, with females being generally more affected than males. Adverse childhood experiences are known to increase the risk of developing psychopathologies and DNA methylation was demonstrated to drive the long-lasting effects of early life stress and promote stress susceptibility. Methyl-CpG binding protein 2 (MECP2), an X-linked reader of the DNA methylome, is altered in many mental disorders of stress origin, suggesting MECP2 as a marker of stress susceptibility; previous works also suggest a link between MECP2 and early stress experiences. The present work explored whether a reduced expression of MECP2 is paralleled by an increased vulnerability to the negative outcomes of stress exposure during childhood. To this aim, blood MECP2 mRNA levels were analyzed in 63 people without history of mental disorders and traits pertaining to depressive and anxiety symptom clusters were assessed as proxies of the vulnerability to develop stress-related disorders; stress exposure during childhood was also evaluated. Using structural equation modeling, we demonstrate that reduced MECP2 expression is accompanied by symptoms of anxiety/depression in association with exposure to stress in early life, selectively in healthy women. These results suggest a gender-specific involvement of MECP2 in the maladaptive outcomes of childhood adversities, and shed new light on the complex biology underlying gender bias in stress susceptibility.
Gesehen am 31.01.2023